ARAH PENGATURAN HUKUM PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI KAMPUS MENURUT PERATURAN MENTERI PENDIDIKAN, KEBUDAYAAN, RISET, DAN TEKNOLOGI NOMOR 30 TAHUN 2021 TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI - Nadhira Diva Saraswati; Pan Lindawaty Suherman Sewu (Universitas Suryakancana, 2022)
The rising number of sexual violences commited in some universities is the background for the issuance of Regulation of Ministry of Education, Culture, Research, and Technology Regulation Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education (hereinafter abbreviated as Permendikbudristek No 30 of 2021). It is hoped that this arrangement can be used as a means to prevent and deal with sexual violence that occurs in the university environment. The purpose of this research is to find out how the Ministry of Education and Culture or the Ministry of Education and Culture determines the results of its policies in dealing with cases of sexual violence in the campus environment. The type of research used is normative juridical law research which is carried out by combining legal materials that focus on positive legal norms, consisting of secondary data as main data and primary data as supporting data. Permendikbudristek No. 30 of 2021 is needed by the Academic Community to implement one of the rights of the Indonesian people as stated in Law No. 39 of 1999 concerning Human Rights, where everyone has the right to feel safe and receive protection against threats. In addition, Permendikbudristek No. 30 of 2021 is needed so that the objectives of the Indonesian state as stated in the 1945 Constitution are achieved, namely promoting general welfare, and educating the life of the Indonesian nation. Legal arrangements for the prevention and handling of sexual violence on campus that have been regulated by the government are the basis and guidelines for the rules, but the prevention and handling of sexual violence in universities can only be successful if it is supported by a